(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The auditor plays a key role in economic life because of the confidence his report adds to the audited financial statements. In applying the various stages of the audit process, the auditor must maintain a high moral level that determines his type of commitment in his professional behavior before God first, And to the society at last in a way that supports its independence. On this basis, the aim of the research is to identify the threats that affect the independence of the auditor. To achieve the objective of the research, the hypothesis that there is a statistically significant relationship between the threats facing the auditor and his professional independence was formulated. In the light of testing the hypotheses of research it was concluded that the financial interests of the auditor with the client could affect the independence of the auditor, and that the risks of self-revision may affect the independence of that auditor also, and that unprofessional harmony and the auditor’s defense of the client’s interests can also affect the independence Checker.